Genomic approaches to understanding population divergence and speciation in birds. (21st October 2015) - Toews, David P. L.; Campagna, Leonardo; Taylor, Scott A.; Balakrishnan, Christopher N.; Baldassarre, Daniel T.; Deane-Coe, Petra E.; Harvey, Michael G.; Hooper, Daniel M.; Irwin, Darren E.; Judy, Caroline D.; Mason, Nicholas A.; McCormack, John E.; et al.
Abstract: The widespread application of high-throughput sequencing in studying evolutionary processes and patterns of diversification has led to many important discoveries. However, the barriers to utilizing these technologies and interpreting the resulting data can be daunting for first-time users. We provide an overview and a brief primer of relevant methods (e.g., whole-genome sequencing, reduced-representation sequencing, sequence-capture methods, and RNA sequencing), as well as important steps in the analysis pipelines (e.g., loci clustering, variant calling, whole-genome and transcriptome assembly). We also review a number of applications in which researchers have used these technologies to address questions related to avian systems. We highlight how genomic tools are advancing research by discussing their contributions to 3 important facets of avian evolutionary history. We focus on (1) general inferences about biogeography and biogeographic history, (2) patterns of gene flow and isolation upon secondary contact and hybridization, and (3) quantifying levels of genomic divergence between closely related taxa. We find that in many cases, high-throughput sequencing data confirms previous work from traditional molecular markers, although there are examples in which genome-wide genetic markers provide a different biological interpretation. We also discuss how these new data allow researchers to address entirely novel questions, and conclude by outlining a number of intellectual and methodological challenges as the genomics era moves forward.